Integrasi Literasi Finansial dalam Kurikulum Sekolah - Wibowo, Wahyu (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
Financial literacy is an important skill needed by individuals to manage their finances wisely. However, the level of financial literacy in Indonesia still needs to be improved even though the financial inclusion rate continues to grow. This study aims to explore the importance of integrating financial literacy into the school curriculum and compare its implementation in various countries. Using a literature study method with a descriptive-critical approach, this study analyzes various academic sources and policies related to financial education. The results show that countries such as Finland, Australia, Belgium, and the United States have successfully implemented financial literacy systematically in their curriculum, with a practice-based and technology-based approach. In Indonesia, the main obstacles to implementing financial literacy in schools include limited resources, lack of teacher training, and social norms that still consider discussions about finance as taboo. Although several initiatives have been carried out, such as adjusting the curriculum with financial material across subjects, their effectiveness is still limited. Therefore, a more contextual learning model is needed and policies that support the implementation of comprehensive financial literacy in schools. Integrating financial literacy into education will help equip the younger generation with better economic skills, ensure their readiness to face the challenges of the digital economy, and contribute to the stability of the national economy in the future.